Complex pastern injuries involving the scutum medium in ten horses. (20th March 2020) - Bergstrom, T.; Bass, L.; Daglish, J.; Moorman, V.; Griffin, J.; Barrett, M.
Summary: No description of injuries to the equine scutum medium exists in the veterinary literature. The purpose of this case series is to describe the clinical findings, diagnostic imaging findings, treatment and outcome of 10 horses with complex pastern injuries involving the scutum medium. Horses with scutum medium injury presented with septic synovial structures, acute lameness or chronic lameness. In all cases, scutum medium injury occurred with severe tendon, ligament or osseous injuries in the pastern region. The most common comorbidities were proximal interphalangeal joint sepsis, injuries to the straight sesamoidean ligament and/or the superficial digital flexor tendon branches. This case series also highlights that severe injuries to the scutum medium can be associated with proximal interphalangeal joint subluxation. Outcome and treatment are dependent upon concurrent injuries but proximal interphalangeal joint arthrodesis should be considered. Prognosis for return to athletic function is poor, and return to pasture soundness is guarded.